The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1163/22134808-20191450
|View full text |Cite
|
Sign up to set email alerts
|

The Shepard–Risset Glissando: Identifying the Origins of Metaphorical Auditory Vection and Motion Sickness

Abstract: Abstract We recently showed that auditory illusions of self-motion can be induced in the absence of physically accurate spatial cues (Mursic et al., 2017). The current study was aimed at identifying which features of this auditory stimulus (the Shepard–Risset glissando) were responsible for this metaphorical auditory vection, as well as confirming anecdotal reports of motion sickness for this stimulus. Five different types of auditory stimuli were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…A depiction of the visual content of the abstract and naturalistic conditions can be found in Figure 3 A and B, respectively. The abstract auditory stimulus was an ascending Shepard-Risset glissando which has been shown to elicit vection [38], [39]. The naturalistic auditory stimulus was the sound of a train departing.…”
Section: Designmentioning
confidence: 99%
“…A depiction of the visual content of the abstract and naturalistic conditions can be found in Figure 3 A and B, respectively. The abstract auditory stimulus was an ascending Shepard-Risset glissando which has been shown to elicit vection [38], [39]. The naturalistic auditory stimulus was the sound of a train departing.…”
Section: Designmentioning
confidence: 99%
“…The naturalistic auditory stimulus was the sound of a departing train, whereas the abstract auditory stimulus was an ascending Shepard-Risset glissando. Previous research has shown that the Shepard-Risset glissando can induce auditory vection (Mursic et al, 2017;Mursic & Palmisano, 2020). The third IV was the secondary task participants were expected to perform.…”
Section: Designmentioning
confidence: 99%
“…The naturalistic auditory stimulus was the sound of a train departing. The abstract auditory stimulus was an ascending Shepard-Risset glissando as previous research on auditory vection has shown that the Shepard-Risset glissando elicits vection (Mursic et al, 2017;Mursic & Palmisano, 2020). We have obtained the Shepard-Risset audio sample from the same source as used by Mursic et al (2017).…”
Section: Designmentioning
confidence: 99%